OPTIMIZING PUBLIC SERVICES THROUGH ADMINISTRATIVE DIGITIZATION AT THE TAMALANREA SUBDISTRICT OFFICE - Munizu, Musran; Zakaria, Nanang; Fitriani, Aida (TOPLAMA, 2025)
This study aims to optimize public services through the digitization of administration at the Tamalanrea Subdistrict Office using the ABC (Action-Based Collaboration) approach, which consists of three stages: needs assessment, digital system development, and community empowerment. This method was chosen to ensure that the resulting solutions are evidence-based, participatory, and sustainable. Data collection was conducted through in-depth interviews with subdistrict officials and the community, field observations, and document analysis to identify challenges in the manual administrative system. The research results show that the implementation of the digital system was able to increase service efficiency by 72%, reduce document processing time from 5-7 days to 1-2 working days, and increase the Community Satisfaction Index (CSI) from 65 to 86. Additionally, digitalization successfully curbed illegal fees and improved transparency through real-time tracking features. Intensive training for village officials increased digital competencies by 75%, while community outreach encouraged 89% of users to adopt the application. However, the study also identified challenges such as resistance from some senior staff and limited internet connectivity in certain areas. Overall, this research demonstrates that a collaborative approach to administrative digitalization not only accelerates service processes but also strengthens accountability and inclusivity. These findings provide policy recommendations for local governments to expand digital transformation at the village level, taking into account infrastructure and human resource capacity.